H(2)S gas sensitive indium-doped ZnO thin films: preparation and characterization - Badadhe, Satish S.; Mulla, Imtiaz S. (Sensors and Actuators B-Chemical, 2009)
High quality indium-doped ZnO (IZO) thin films (similar to 100 nm) have been deposited onto the glass substrates by using a conventional spray pyrolysis technique. Precursors such as zinc acetate, indium chloride with Brij-35 (polyoxyethylene lauryl ether) as a non-ionic surfactant were used. The morphology, crystal structure, elemental analysis and the gas response properties were investigated by using SEM, TEM, XRD, AFM and XPS techniques. The films show hexagonal wurtzite structure which reveal variations in (100). (00 2) and (10 1) intensities with indium doping. The crystallite size calculated by Scherrer formula was in the range of 30-50 nm. The SEM and AFM analysis show 50-70 nm sized grains, while the TEM confirms formation of grains by similar to 10nm sized particles. Their response towards various gases was measured at different operating temperatures and different levels of In-dopants. The 3 at% In-doped ZnO showed response as high as 13,000 for 1000ppm H(2)S at 250 degrees C. It exhibited fast response (similar to 2s) and recovery time (similar to 4 min). The gas response strongly depends on the morphology and indium concentration. The high gas response of IZO is explained on the basis of thickness dependent trap state density. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Hydrogen sulfide sensor; Indium oxide; Spray pyrolysis; thin film; Zinc oxide